PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN LIVEWORKSHEET UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Ika Fachrina Putri; Wahyu Budi Sabtiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to describe the improvement of students' critical thinking skills, the implementation of learning, and student responses through the application of the guided inquiry learning model assisted by Liveworksheet on the topic of mixture separation. This quantitative study employed a Pre-Experimental design with a One Group Pretest-Posttest pattern. The subjects were 31 students of class VIII-H at SMPN 3 Sidoarjo in the even semester of the 2025/2026 academic year. Data were collected using critical thinking skill tests, learning implementation observation sheets, and student response questionnaires. The results showed an improvement in critical thinking skills with an average N-Gain of 0.83 (high category), where 74.2% of students reached the high category. The Wilcoxon test resulted in an Asymp. Sig. value of 0.000 (< 0.05), proving a significant difference between pretest and posttest scores. The learning implementation reached an average of 94.04% in the first meeting and increased to 100% in the second meeting, categorized as